Melhoria na precisão dos resultados em termoeconomia devido à desagregação da exergia e construção racional do diagrama produtivo - Colombo, Daniel Corona (2016)
Given the growing energy demandsprojected for the next years and oil depletion, it is increasinglynecessary the application of techniques for the efficient production of electricity and for the rational use of natural resources inthethermal systems. Among these techniques is thermoeconomics analysis that enablethe achievement of systemsoperating more efficiently. In the last decade, the models that propose the thermoeconomics analysisusing disaggregated exergy into its components has beengaining strength.The disaggregated exergy applicationin Thermoeconomicshad as initial aimto increase theaccuracy of the results by means ofthe EMET modelthat disaggregates the physical exergy into its thermical and mechanic components. Subsequently, the disaggregated exergyhas incorporated into its aimthe ability fortreatingappropriatelythe dissipative equipment andresidues. Dissipative equipments treatmentis of great value, especially for Diagnosis and Optimization, the fields of Thermoeconomics thatseekincreasedefficiency in thermal systems. However, the application of models that disaggregate the exergy bringsthe increase in complexity of the thermoeconomicsanalysis. Therefore, it is very important the comparison of manythermoeconomicsmodels appliedto different thermal systems forestablishingthe advantagesand disadvantagesof each methodology. There are studiesthat already madethe comparison between thermoeconomicsmodels, but with the recent emergence of one more exergy disaggregation level (UFS+ model), it is necessary to complement these studieswith the results of this new model. The results of thermoeconomics analysis are strongly influenced by the type of disaggregationthat isused, butthis is not the only factor thataffectsthe results. The way the analyst describes the relation of each productiveunit withothersmust also be observed. Besides, the residuestreatmentis important in order to vary the final analysis’s results. In models that use entropy as part of the exergy, the physicalresiduestreatmentis well-defined and showno inconsistency. However, the chemical residuesweretreated in such a way that the exergy balance is not satisfied in burners of thermal systemsand this is seen as a thermodynamicsinconsistency. Overall, the aimof this work is to complementand to consolidatestudiesthat makethe comparison between thermoeconomicsmodelsof exergy disaggregation,to show how different descriptions of the productiveprocesscanaffectthe analysis andtopoint out the inconsistency generated by thermoeconomicsmodels when thechemical residuesare treated in differents ways